P213 Pro(tect) service – engaging with male sex workers. (18th May 2015) - Stockwell, Sarah; Dean, Gillian; Tweed, Mark; Boyt, Tom
Abstract : Background/introduction: Pro(TECT), a bespoke service for male sex workers (MSW), was launched in June 2014 by THT to engage with local high-risk MSM. Motivational interviewing (MI) is used to explore behaviour change; clients are offered a wide range of support to improve sexual health and reduce onward STI/HIV transmission. Analysis of behaviour and service evaluation was performed at 6 months. Methods: All clients (15) completed an online survey regarding sexual practices, drug/alcohol use and experience of the service. Results: In the last 12 months: 70% reported insertive UAI; 40% receptive UAI; 36% diagnosed with an STI; 29% HIV positive; 21% injected drugs; 43% under the influence of drugs/alcohol while selling sex; 33% self-harmed in last 12 months. Conclusions: Unprotected sex is common among MSW. Early MI results show good improvement in knowledge and risk taking behaviour. High levels of drug/alcohol use and self-harm require close links to mental health services. Pro(TECT) is unique in accessing this 'hard-to-reach' population and offers a holistic service of harm reduction.